2021
DOI: 10.1002/rcm.9065
|View full text |Cite
|
Sign up to set email alerts
|

Strategies to overcome interferences in elemental and isotopic geochemical analysis by quadrupole inductively coupled plasma mass spectrometry: A critical evaluation of the recent developments

Abstract: Quadrupole Inductively Coupled Plasma Mass Spectrometry (ICP‐MS) instruments were introduced into geochemical and mineral exploration laboratories nearly four decades ago, providing a technique that could meet their longstanding requirement for the precise and accurate determination of several groups of trace elements and isotopes in geological materials such as rocks, minerals, ores, soils, sediments, and natural water samples. Despite its popularity among geochemists, the technique suffered from spectral and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 36 publications
(26 citation statements)
references
References 152 publications
0
24
0
2
Order By: Relevance
“…Due to spectral interferences, the determination of lower concentrations (ng/mL order or lower) of P, S, Si, Cl, Br, and I is often challenging for traditional ICP-MS. Measurement by ICP-QMS/QMS at massshift mode using O2 as the cell gas permitted a better performance for analysis of these element and has been reported for P, 15,19,34,41,45,[49][50][51][52] S, 15,19,34,40,41,45,[44][45][46][47][48][49][50][51][52] Si, 19,34,45,50,52 Cl, 34,45,52 Br, 34,41 and I, 34,41 respectively.…”
Section: Reaction Gases Used In the Measurement By Icp-qms/qmsmentioning
confidence: 99%
“…Due to spectral interferences, the determination of lower concentrations (ng/mL order or lower) of P, S, Si, Cl, Br, and I is often challenging for traditional ICP-MS. Measurement by ICP-QMS/QMS at massshift mode using O2 as the cell gas permitted a better performance for analysis of these element and has been reported for P, 15,19,34,41,45,[49][50][51][52] S, 15,19,34,40,41,45,[44][45][46][47][48][49][50][51][52] Si, 19,34,45,50,52 Cl, 34,45,52 Br, 34,41 and I, 34,41 respectively.…”
Section: Reaction Gases Used In the Measurement By Icp-qms/qmsmentioning
confidence: 99%
“…Certainly, the geochemical analytical techniques have witnessed a powerful shift toward ICP-MS technology since 1983 when the first commercial ICP-MS instruments were released. Further instrumental developments in ICP-MS led to the development of HR-ICP-MS and MC-ICP-MS, and also the incorporation of a variety of interference removal technologies which had a greater impact on the quality of geochemical data (both elemental and isotopic), although several other analytical techniques including AAS, XRF, INAA, and ICP-OES are also available for geochemical analysis [22][23][24]. The newly developed MP-AES with its promising performance was also extensively utilized in recent years for the analysis of most complex geological materials such as rocks and ores and is becoming established slowly as a promising alternative analytical technique to AAS and ICP-AES for geochemical analysis [25,26].…”
Section: Contributions From the Recent Advances In Analytical Instrum...mentioning
confidence: 99%
“…The RSD of less than 3% is considered good precision for concentrations varying in the range of 1000s of µg/g, while it can be less than 10% for those ultra-trace concentrations in sub-ng/g levels. The use of internal standardization is the proper remedy to this kind of problem [24].…”
Section: Short and Long-term Precision During Analysismentioning
confidence: 99%
“…2020) demonstrated that by using the portable infrared mineral analyzer (PIMA) using SWIR spectral analysis it is possible to get both qualitative and quantitative results of mineral components and geochemistry (e.g., La, Ce, Pr, Nd, Sm, Gd, Dy, Er, Yb, and Y) on board in previously studied ocean-floor areas, with high sensitivity. This instrument can also replace the destructive wet chemical sample digestion and extraction, and analysis by conventional ICP-MS (Balaram 2021b). Thus, obtaining empirical SWIR-reflectance data by SWIR spectral analysis in near real-time can be valuable in exploration of geochemical deposits in the ocean floor particularly to make any changes in exploration strategies Traditional laboratory-based instruments like WD-XRF, ICP-MS, and Raman spectrometer are normally housed in stationary locations with controlled environment and temperature.…”
Section: Role Of Portable Analytical Tools/sensors In Deep-sea Explor...mentioning
confidence: 99%
“…This method minimizes matrix effects due to compatibility between sample chemical and physical characteristics and calibration standards. Other traditional calibration strategies such as standard addition (SA) and internal standardization (IS) can be utilized to reduce matrix effects (Balaram, 2021b). To minimize the influence of the matrix elements on a particular element, matrix-matched international CRMs are analyzed and correction factors are applied to get the most accurate data even in field conditions.…”
Section: Role Of Portable Analytical Tools/sensors In Deep-sea Explor...mentioning
confidence: 99%